The impact of toxic metals on vineyards and wines and the agronomical practices to decrease their content - Mosca, Caterina (2020)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto